WHO-listed authorities (WLA) framework: transparent evidence-based approach for promoting regulatory reliance towards increased access to quality-assured medical products - Broojerdi, Alireza Khadem; Salvati, Anna Laura; Abdelfattah, Mohammed Refaat; Dehaghi, Razieh Ostad Ali; Sillo, Hiiti B.; Gaspar, Rogerio (Frontiers in Medicine, 2024)
Background Increased global access to safe, effective and quality-assured medical products remains a primary goal for the full realization of the World Health Assembly Resolution WHA 67.20 on regulatory systems strengthening for medical products as well as target 3.8 of the Sustainable Development Goals (SDG). To promote the development of efficient regulatory systems, the WHO introduced the Global Benchmarking Tool (GBT) in 2016, upon which the WHO–Listed Authority (WLA) framework was later established. This study aimed to appraise the development of the WLA framework across various phases while highlighting its achievements, challenges, and areas for improvement. Methods An exploratory study design using a qualitative approach was used to gather information from relevant documents as well as views and experiences from purposefully selected participants from diverse backgrounds. Data was collected using a combination of desk reviews and In-depth one-to-one or small group interviews employing semi-structured interview guides with open-ended questions. Data was analysed using an inductive thematic analysis approach. Results The leading role of the WHO was noted in developing and implementing essential documents and mediating consultative processes among stakeholders. The framework was revealed to bring an evidence-based, inclusive, and transparent approach to recognizing regulatory authorities (RAs) operating at the highest standards of performance. The framework was anticipated to promote regulatory reliance among all RAs, the WHO’s prequalification programme, and procurement agencies. Furthermore, remarkable progress towards WLA listing was noted among transitional WLAs including the Stringent Regulatory Authorities (SRAs). Challenges related to the availability of resources, resistance to change, and complexity were associated with the framework. Conclusion The study provides a well-rounded view with regard to the roles of the WHO, Member States and other stakeholders in establishing and operationalizing the WLA framework. Furthermore, evaluating the performance and possible WLA designation of RAs operating at international regulatory standards underscores its high relevance in contributing to public health globally. Maintenance along with timely addressing of highlighted next steps to improve the framework particularly in creating better understanding, more communication, and coordination are highly encouraged.